Usability evaluation of Web-based GIS by means of a model - Komárková, Jitka; Sedlák, Pavel; Habrman, Jakub; Čermáková, Ivana (IEEE (Institute of Electrical and Electronics Engineers), 2017)
Spatial information is required by many users to support their decision-making. Application that provide spatial information may be quite complicated so evaluation of their usability is very important. Usability evaluation can help to improve their design or how to choose better application. Many various methods have been proposed. The paper describes a case study which uses combination of usability user testing and NGOMSL model to evaluate usability of chosen Web-based applications by means of calculating a utility. Case study shows that very similar results are obtained by both methods. Average time necessary for usability evaluation is shorter in the case of NGOMSL model.
Hodnocení použitelnosti webových GIS založených na modelech
Keywords: NGOMSL; Usability; user testing; Web-based GIS; NGOMSL; Použitelnost; Uživatelské testování; Webové GIS